Randomised trial of a social media-based lifestyle intervention program for the prevention of non-communicable diseases in adults : project SWAY - Wood, Paola Silvia (University of Pretoria, 2022)
Thesis (PhD (Sport Science (Biokinetics)))--University of Pretoria, 2021.